Программная реализация единого информационного пространства интегрированной системы автоматизированного проектирования «Турбоагрегат» - Бойко, А.В.; Говорущенко, Ю.Н.; Усатый, А.П. (Электронное моделирование, 2009)
The features of software realization of information space of integrated Turboagregat CAD system are considered on the basis of principles of an openness, information and system unity with the use of the special description of a structural-topological configuration of information space and presentation of all its elements, components and subsystems in a unified form, that has allowed to organize the processes of control and information coordination with the help of universal recursive algorithms.